2015
DOI: 10.1097/qai.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Trends in HIV Nonoccupational Postexposure Prophylaxis Use at a Boston Community Health Center Between 1997 and 2013

Abstract: Secular trends in non-occupational post-exposure prophylaxis (NPEP) use have not been well-characterized. We performed a retrospective longitudinal study of 894 electronic medical records of NPEP users, mostly men who have sex with men, at a Boston community health center who presented between July, 1997 and August, 2013. NPEP use and condomless sexual exposures increased over time; 19.4% had multiple NPEP courses. Having an HIV-infected partner was associated with increased odds of regimen completion, and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
3
14
1
Order By: Relevance
“…We found that only 6.5% of all persons repetitively showed up at the ER for PEP. This number is substantially lower than the 20% reported in previous studies [32][33][34][35] and, thus, suggests that PEP is unlikely to promote higher sexual risk behavior, which is consistent with a report by Martin et al [36]. However, persons with high-risk sexual behavior, presenting repetitively for PEP, most likely would be the ideal candidates for HIV PrEP.…”
Section: A C C E P T E Dsupporting
confidence: 84%
“…We found that only 6.5% of all persons repetitively showed up at the ER for PEP. This number is substantially lower than the 20% reported in previous studies [32][33][34][35] and, thus, suggests that PEP is unlikely to promote higher sexual risk behavior, which is consistent with a report by Martin et al [36]. However, persons with high-risk sexual behavior, presenting repetitively for PEP, most likely would be the ideal candidates for HIV PrEP.…”
Section: A C C E P T E Dsupporting
confidence: 84%
“…As we learn lessons from “real-world” experiences about how best to implement PEP and PrEP, the transition from PEP to PrEP will also require active investigation, since some patients who receive PEP may engage in recurrent high-risk behaviors [107, 108] and may therefore benefit from ongoing chemoprophylaxis to prevent HIV acquisition. Unfortunately, the awareness of NPEP has been limited even among high-risk MSM, as demonstrated by several studies [109111].…”
Section: Pre-exposure Prophylaxis (Prep)mentioning
confidence: 99%
“…More recently, newer medications have been developed that are better tolerated. The use of tenofovir disoproxil fumarate (TDF) instead of AZT as part of a PEP regimen has been associated improved tolerability and higher completion rates, offering the promise of fewer seroconversions (17, 18). …”
Section: Introductionmentioning
confidence: 99%